2012
DOI: 10.1128/jb.00782-12
|View full text |Cite
|
Sign up to set email alerts
|

CbrA Is a Flavin Adenine Dinucleotide Protein That Modifies the Escherichia coli Outer Membrane and Confers Specific Resistance to Colicin M

Abstract: ABSTRACTColicin M (Cma) is a protein toxin produced byEscherichia colithat kills sensitiveE. colicells by inhibiting murein biosynthesis in the periplasm. Recombinant plasmids carryingcbrA(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
(54 reference statements)
3
14
0
Order By: Relevance
“…Thus, it was proposed that in the natural environment with a limited supply of nutrients, CbrA protects sensitive cells from colicin M synthesized by competitors. Furthermore, CbrC, which we also found to be induced by colicin M treatment, has been shown to protect against colicin E2 and also seems to be involved in alteration of outer membrane structure [41]. Our results indicate that subinhibitory concentrations of colicin M could induce protection against colicins.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, it was proposed that in the natural environment with a limited supply of nutrients, CbrA protects sensitive cells from colicin M synthesized by competitors. Furthermore, CbrC, which we also found to be induced by colicin M treatment, has been shown to protect against colicin E2 and also seems to be involved in alteration of outer membrane structure [41]. Our results indicate that subinhibitory concentrations of colicin M could induce protection against colicins.…”
Section: Resultssupporting
confidence: 60%
“…The two-component CreBC system positively controls transcription of cbrA . Recently, the CbrA protein was shown to protect against colicin M and osmotic shock, implying a function of CbrA in outer membrane structure [41]. Thus, it was proposed that in the natural environment with a limited supply of nutrients, CbrA protects sensitive cells from colicin M synthesized by competitors.…”
Section: Resultsmentioning
confidence: 99%
“…In- terestingly, subinhibitory concentrations of colicin M induce the transcription of genes involved in adaptive responses, including the two-component CreBC system associated with increased resistance to some colicins (45). Recent studies have demonstrated that CbrA, being a nonessential protein, confers high resistance to colicin M and renders cells resistant to osmotic shock in a CreBCdependent manner (46). On the other hand, the overproduction of YieJ (formerly CbrC) enhances the tolerance of colicin E2 (a role previously assigned to CreD).…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanism of action of the Cmi immunity protein still remains unknown. More recently, the overexpression of an E. coli gene named cbrA (formerly yidS) was shown to render cells specifically resistant to ColM (15). Based on the sequence similarities it exhibits with geranylgeranyl reductases (GGR) and other FAD-dependent oxidoreductases, Helbig et al suggested that the CbrA protein might function as a reductase of isoprenoid molecules.…”
Section: Introductionmentioning
confidence: 99%